Splenic Volume, an Easy-To-Use Predictor of HCC Late Recurrence for HCC Patients After Hepatectomy - Fang, Tongdi; Long, Guo; Mi, Xingyu; Su, Wenxin; Mo, Lei; Zhou, Ledu (Frontiers in Oncology, 2022)
Purpose The high recurrence rate of hepatocellular carcinoma (HCC) has a poor impact on the quality of life and survival time of patients. Especially for late recurrence, poor data are available in analysis. We aim to evaluate whether the splenic volume (SV) measured from preoperative CT images could predict late recurrence in HCC patients after hepatectomy. Patients and Methods A cohort of 300 HCC patients hospitalized at Xiangya Hospital of Central South University between January 2015 and June 2018 was retrospectively analyzed. The SV was calculated by using automated volumetry software from preoperative CT images. A total of 300 HCC patients were separated into the early recurrence cohort (n=167), the late recurrence cohort (n=39), and the no recurrence cohort (n=94) according to whether there is a recurrence and the recurrence time. Univariate and multivariate Cox analyses were performed to identify the independent risk factors of both early and late recurrence. Results AFP, Microvascular invasion (MVI), satellitosis, and BCLC staging were independent risk factors of HCC early recurrence. Splenic volume (HR=1.003, 95%CI:1.001-1.005, P<0.001) was the only predictor of HCC late recurrence. Based on X-tile software, 133 non-early recurrence patients were divided into two groups according to SV: low SV (<165ml, n=45) and high SV (≥165ml, n= 88). The low SV group had a significantly better RFS compared with the high SV group (P=0.015). Nomogram was built on the base of SV to get the probability of 3-year RFS, 4-year RFS, and 5-year RFS. Conclusion In our study, we drew a conclusion that splenic volume was the only predictor of HCC late recurrence because of its association with portal hypertension and liver cirrhosis. High splenic volume often indicated a worse recurrence.